CLINICAL OUTCOMES OF PERCUTANEOUS CORONARY INTERVENTION WITH DRUG ELUTING STENT IN STABLE ANGINA PATIENTS - D. I. Tomilova; Yu. A. Karpov; V. V. Lopukhova (Российский кардиологический журнал, 2017)
Aim. To evaluate the occurence of cardiovascular events (CVE) and influence of lipid parameters on it, as other clinical and instrumental factors of coronary heart disease (CHD) patients during 5 years after selective percutaneous coronary intervention (PCI) with drug eluting stenting (DES).Material and methods. In the study, 574 patients included, with stable angina (81% males, mean age 60,3 y. o.), hospitalized to the FSBI RCSPC of MHRF for selective PCI with implantation of DES. Patients were prescribed the therapy according to stable angina guidelines, including statins. The analysis was done, of various clinical and instrumental and laboratory parameters for evaluation of prognostic significance. The endpoints were assessed: lethal cases from cardiovascular, as from all causes, non-fatal myocardial infarction (MI), non-fatal stroke, repeated coronary revascularization, that happened after discharge.Results. During the entire follow-up (average 53,5 months), CVE were registered in 24% cases. Totally, died 29 patients (5,1%), of those 4 (0,7%) — from non-cardiac causes, and repeat revascularization was done in 84 (14,6%) patients, non-fatal MI and stroke developed in 17 (3,0%) and 8 (1,3%), respectively. The risk factors were defined, that are related with the rate of fatal outcomes: smoking, brachiocephalic atherosclerosis, stroke in anamnesis, significant lesion of circumflex artery (CA) and its branches. Non-fatal stroke developed more oftenly in patients with higher body mass index (BMI) (32,2±2,56 versus 28,15±4,22, p=0,0164). Non-fatal MI more oftenly registered in patients with higher number and length of implanted stents (p=0,0018 and p<0,0001, resp.). By the end of follow-up, there were 66,2% patients on statins treatment. Target low density lipoproteides cholesterol (LDL-C) level (<1,8 mM/L) was found in 8,7%, median LDL-C level was 2,8 mM/L. There were no significant differences in LDL-C between those taking statins and discontinued,during 5 years. There was no significant relation of lipid profile values with CVE as well. The number of fatal cases was higher in the group of patients with lower baseline high density lipoproteide cholesterol. Conclusion. Adverse events were found in about quarter of patients. Most of patients did not reach the target LDL-C. There was no significant relation in baseline LDL-C and its level in 5 years, with the occurence of MI, stroke, repeat revascularizations, all cause deaths. This can be explained by the absence of significant differences in LDL-C levels in patients continuing and discontinued statins during the follow-up, and is related to the use of insufficient statins dosages and low adherence to statin treatment.